Pretreatment of palm oil waste via torrefaction process - Hazrina, Abdul Halim (2015)
Recently, the demand of energy increase as the population of the world keep increasing from years to another years. However the energy sources is not sufficient to survive with the demands. Malaysia is experiencing drastic growth in population and economy and requires exploring alternative energy sources to cope its population and commercial energy demand. Biomass as the fourth largest energy resource in the world is abundant in the country. Malaysia is one of the largest producer of palm oil industries have generated huge amount of biomass from palm oil. There are many types of biomass residue generated by the palm oil industry which includes fronds, trunks, empty fruit bunches (EFB), palm mesocarp fiber (PMF), and palm kernel shell (PKS). In general, oil forms about 10% of the whole oil palm trees while the other 90% remains as biomass. All those biomass are either utilized or discarded at the plantation or palm oil mills. In this study, three types of biomass were treated by using torrefaction process. Torrefaction process is strongly depended on thermal decomposition behaviour and composition of lignocellulosic constituents. Based on the torrefaction process, the moisture contents decreases of as temperature increases. The mass yield of EFB, PKS and PMF decreases as the temperature increase. For EFB, increasing of the temperature resulted in higher heating value. However, the heating value of PMF and PKS show the highest value at temperature 270°C. Palm mesocarp fiber and palm kernel shell exhibit excellent energy yield values which are higher than 90%. Empty fruit bunch, on the other hand, exhibited a rather poor energy yield of 70%.